The influence of the organizational and environmental factors on the Amazon family farming enterprises in Brazil (Research, Society and Development, 2021)
This study analyzed whether organizational and environmental factors influence the management of productive units of Amazonian family farmers. The method used consisted of an in-depth study of 32 communities in the northeast of Pará, using questionnaires, whose data were analyzed using Pearson's correlation analysis, and structured interviews, whose data were analyzed with French help technique of content analysis. The results showed the variables that most influence the management of the productive units are financial, among the organizational factors, and the economic and environmental, among the environmental factors. The conclusion showed that the surveyed family farmers' pre-capitalist mentality is the main impediment to achieving their business success.